IGF2BP1 promotes SRF-dependent transcription in cancer in a m6A- and miRNA-dependent manner. Issue 1 (29th October 2018) - Müller, Simon; Glaß, Markus; Singh, Anurag K; Haase, Jacob; Bley, Nadine; Fuchs, Tommy; Lederer, Marcell; Dahl, Andreas; Huang, Huilin; Chen, Jianjun; Posern, Guido; Hüttelmaier, Stefan
Abstract: The oncofetal mRNA-binding protein IGF2BP1 and the transcriptional regulator SRF modulate gene expression in cancer. In cancer cells, we demonstrate that IGF2BP1 promotes the expression of SRF in a conserved and N 6 -methyladenosine (m 6 A)-dependent manner by impairing the miRNA-directed decay of the SRF mRNA. This results in enhanced SRF-dependent transcriptional activity and promotes tumor cell growth and invasion. At the post-transcriptional level, IGF2BP1 sustains the expression of various SRF-target genes. The majority of these SRF/IGF2BP1-enhanced genes, including PDLIM7 and FOXK1, show conserved upregulation with SRF and IGF2BP1 synthesis in cancer. PDLIM7 and FOXK1 promote tumor cell growth and were reported to enhance cell invasion. Consistently, 35 SRF/IGF2BP1-dependent genes showing conserved association with SRF and IGF2BP1 expression indicate a poor overall survival probability in ovarian, liver and lung cancer. In conclusion, these findings identify the SRF/IGF2BP1-, miRNome- and m 6 A-dependent control of gene expression as a conserved oncogenic driver network in cancer.